The Role of Elementary School Age in Playing in Early Childhood Social Development - Hutagalung, Ahmad Ichsan Yafi (JOYCED: Journal of Early Childhood Education, 2024)
Playing is a fun activity for children. With this activity, of course, it can develop social skills because of the interaction that is established. This study aims to determine and analyze the role of age when playing in the social development of early childhood. This type of research uses a qualitative descriptive method with a case study of RA Al-Qur'an Iqro and SD Muhammadiyah 02 Pematangsiantar. The responses in this study were from all RA and SD children who often play together, teachers, and principals. Data collection techniques were by interview, observation, and documentation. The results of this study indicate that the role of elementary school age can help the social development of early childhood. In addition to being able to socialize with peers, RA children also dare to deal with those older than them. In addition, there are several findings in playing activities such as: 1) elementary school children can listen attentively; 2) use good words; 3) play in turns.